Data Structures using C : A Practical Approach for Beginners. - Jagtap, Amol M.; Mali, Ajit S. ([Place of publication not identified] : Chapman and Hall/CRC, 2021)
The data structure is a set of specially organized data elements and functions, which are defined to store, retrieve, remove and search for individual data elements. Data Structures using C: A Practical Approach for Beginners covers all issues related to the amount of storage needed, the amount of time required to process the data, data representation of the primary memory and operations carried out with such data. Data Structures using C: A Practical Approach for Beginners book will help students learn data structure and algorithms in a focused way. Resolves linear and nonlinear data structures in C language using the algorithm, diagrammatically and its time and space complexity analysis Covers interview questions and MCQs on all topics of campus readiness Identifies possible solutions to each problem Includes real-life and computational applications of linear and nonlinear data structures This book is primarily aimed at undergraduates and graduates of computer science and information technology. Students of all engineering disciplines will also find this book useful.
1. Fundamental Principles of Algorithm and Recursion2. Sequential Representation of Linear Data Structures3. Void Pointer and Dynamic Memory Management4. Linked Representation of Linear Data Structures5. Nonlinear Data Structures: Trees6. Nonlinear Data Structures: Graph7. Searching and Sorting Techniques
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Programming / Algorithms; COMPUTERS / Programming Languages / C; COMPUTERS / Programming Languages / C++; Data structures (Computer science); C (Computer program language)